1999
DOI: 10.1046/j.1432-1327.1999.00599.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of sulphated and nonsulphated forms of cholecystokinin‐58 and their action on gallbladder contraction

Abstract: Cholecystokinin (CCK) exists in multiple molecular forms with different polypeptide lengths and the absence or presence of sulphation. We have isolated sulphated and nonsulphated forms of CCK-58 from porcine intestine and have determined their bioactivities in a guinea-pig gallbladder contraction assay. Both forms co-eluted in cation-exchange chromatography and in several rounds of reverse-phase (RP)-HPLC, but separated upon RP-HPLC using a water/acetonitrile system with heptafluorobutyric acid as counter ion.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 29 publications
1
29
0
Order By: Relevance
“…Other unique roles for CCK58 compared with shorter forms (CCK8 or CCK33) have previously been demonstrated in the modulation of central catecholaminergic mechanisms and neuroendocrine functions [33], the pattern of gallbladder muscle contraction [34,35], and in intestinal afferent nerve discharge [36]. More recently, it was shown that CCK58 inhibited food intake much more strongly than CCK8 by profoundly increasing the intermeal interval (S.W.…”
Section: Resultsmentioning
confidence: 99%
“…Other unique roles for CCK58 compared with shorter forms (CCK8 or CCK33) have previously been demonstrated in the modulation of central catecholaminergic mechanisms and neuroendocrine functions [33], the pattern of gallbladder muscle contraction [34,35], and in intestinal afferent nerve discharge [36]. More recently, it was shown that CCK58 inhibited food intake much more strongly than CCK8 by profoundly increasing the intermeal interval (S.W.…”
Section: Resultsmentioning
confidence: 99%
“…First, canine thyroid C-cells contain mainly nonsulfated CCK-8 and -5 [6], and CCK in human medullary thyroid carcinomas is all nonsulfated CCK-8 [7]. Later it was shown that CCK-58 in the porcine and canine small intestine occurs in both sulfated and nonsulfated form [8,9]. Thus, nonsulfated CCK peptides seem to occur in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…In various CCKs, sulfation of the tyrosine at position 7 from the C-terminus is a posttranslational modification that makes them biologically active peptides (Ma et al, 2006). Varying lengths of CCKs with or without sulfate have been studied for their activities as gastrointestinal hormones (Bonetto et al, 1999) and as CNS players (Rehfeld et al, 2007). Two types of CCK receptors have been identified: CCK1R (CCK-A receptor) and CCK2R (CCK-B receptor).…”
Section: Introductionmentioning
confidence: 99%